STRATEGI PERLAWANAN TERHADAP DOMINASI KEKUASAAN NEGARA DALAM NOVEL LAUT BERCERITA: KAJIAN SUBALTERN - Nurhadini; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This research is entitled "Strategies of Resistance to the Domination of State Power in the Novel Laut Bercerita: A Subaltern Study," which aims to describe the forms of power domination and resistance strategies against the state represented in Leila S Chudori's novel Laut Bercerita. The domination of state power in this novel is depicted through various forms of physical oppression and violence, control and arbitrariness, and mental influence experienced by activist characters. Meanwhile, the resistance strategies carried out by the characters in the novel, such as Biru Laut and his friends, include opening the representation space for subaltern voices, open acts of resistance, and strengthening collective identity and political ideology. The method used in this research is a qualitative method with the type of library research. This refers to a research approach that produces descriptive data in the form of written data as a result of observing an object, namely a novel. The results show that the novel Laut Bercerita strongly represents the conflict between the dominating state power and the struggle of subaltern groups in seizing their existential and political space.